2014
DOI: 10.1155/2014/707529
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Biopsy Sampling Causes Hematogenous Dissemination of Epithelial Cellular Material

Abstract: The extent of epithelial cellular material (ECM) occurring in venous blood samples after diagnostic core needle biopsy (CNB) was studied in 23 patients with CNB diagnosed prostate cancer without provable metastases and 15 patients without cancer. The data show a significant increase of ECM in the peripheral blood sampled 20 seconds or 30 minutes after the last of 10 CNB procedures compared to the number of ECM detectable in the blood samples taken before the performance of CNB. The data indicate that diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…4,7,8 Studies highlight the risk of biopsy-induced tumoremia as demonstrated in 23 prostate cancer patients. 5 They evaluated epithelial cellular material (ECM) based on anticytokeratin antibody anti-CD45 and DAPI. ECM was present in the peripheral blood 39% of cancer patients prebiopsy vs 7% of control subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,7,8 Studies highlight the risk of biopsy-induced tumoremia as demonstrated in 23 prostate cancer patients. 5 They evaluated epithelial cellular material (ECM) based on anticytokeratin antibody anti-CD45 and DAPI. ECM was present in the peripheral blood 39% of cancer patients prebiopsy vs 7% of control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary evidence indicates that tumoremia is precipitated by tumor manipulation during biopsy or surgery, which is a concern given the potential for hematogenous dissemination and distant metastasis. [4][5][6][7][8] We tested the hypothesis that for treatment-naïve PDAC patients, primary tumor endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) induces tumoremia. We determined the peripheral blood plasma cfDNA concentration and detected ctDNA by KRAS 12/13 mutational analysis using digital droplet polymerase chain reaction (PCR).…”
mentioning
confidence: 99%
“…As well, a few cases of breast cancer with the same complication after CNB have been reported [12,13]. There are also studies implying that procedures like prostate biopsy or surgical removal of the tumor during a colonoscopy (in colorectal cancer) may increase the number of circulating tumor cells (CTCs) in the blood in some cases [14,15]. Likewise, animal model studies in mice indicate that a biopsy of the breast tumor might increase the number of CTCs or risk of distant metastasis [16,17].…”
Section: Surgical Biopsymentioning
confidence: 97%
“…In contrast to other cancer types such as pancreatic cancer, routine preventive medical screens for PCa are accessible to a broad spectrum of the public and have been widely accepted, leading to a drastic increase of newly diagnosed PCa cases. Tissue biopsies are invasive and can be associated with adverse effects for the patient [2]. Furthermore, routine tissue biopsy is challenging in metastatic PCa (mPCa).…”
Section: Introductionmentioning
confidence: 99%